Vibrational Spectroscopy-Based Chemometrics Analysis of Clinacanthus nutans Extracts after Postharvest Processing and Extract Effects on Cardiac C-Kit Cells. (23rd February 2022) - Lim, Vuanghao; Chong, Hui Wen; Abdul Samad, Nozlena; Abd Ghafar, Siti Aisyah; Ismail, Ida Shazrina; Mohamed, Rafeezul; Yong, Yoke Keong; Gan, Chee Yuen; Tan, Jun Jie
Abstract : Chemical constituents in plants can be greatly affected by postharvest processing, and it is important to identify the factors that lead to significant changes in chemistry and bioactivity. In this study, attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy was used to analyze extracts of Clinacanthus nutan (C. nutans) leaves generated using different parameters (solvent polarities, solid-liquid ratios, ultrasonic durations, and cycles of extraction). In addition, the effects of these extracts on the viability of cardiac c-kit cells (CCs) were tested. The IR spectra were processed using SIMCA-P software. PCA results of all tested parameter sets were within acceptable values. Solvent polarity was identified as the most influential factor to observe the differences in chemical profile and activities of C. nutans extracts. Ideal extraction conditions were identified, for two sample groups (G1 and G2), as they showed optimal total phenolic content (TPC) yield of 44.66 ± 0.83 mg GAE/g dw and 45.99 ± 0.29 mg GAE/g dw and CC viability of 171.81 ± 4.06% and 147.53 ± 6.80%, respectively. Validation tools such as CV-ANOVA (p < 0.05 ) and permutation ( R 2 and Q 2 plots were well intercepted to each other) have further affirmed the significance and reliability of the partial least square (PLS) model of solvent polarity employed in extraction. Hence, these approaches help optimize postharvest processes that encourage positive TPC and CCs results in C. nutans extracts.